Análisis del perfil y motivación del turista que visita la cuidad de Latacunga en la festividad de la Mama Negra del mes de septiembre del 2023 - Lema Gallo, Alexandra Elizabeth (2024)
The aim this research was to analyze the tourist profile and motivation, who visits the Latacunga city in the Mama Negra party in September. It was used the descriptive research type, due to that has as main aim to collect data and information from the research and exactly describe the activities and objects, with a qualitative approach, it was made, through bibliographic review and interviews. The first aim consisted the description Mama Negra festivity. Getting as a result, what the Santísima Tragedia or Mama Negra is part from Latacungueña culture, this celebration is held in honor from Virgen de las Mercedes, every September 23 and 24. The second aim is to identify the tourist profile and motivation, which it was applied the descriptive-relational research type with a quantitative approach, where it was executed surveys by an instrument, also it was worked with the Likert scale in several questions that facilitates the information collection, it was used a probabilistic sampling, it was necessary to identify the tourists, who visited the Cotopaxi National Park and the Quilotoa Lagoon, which are 355,389 in total, the taken data was from the SNAP (National System of Protected Areas) from year 2021, subsequently to them, they were determined the formula to make the sample, getting a as a response total by 383 surveys. Therefore, it was determined, what it is internal tourism, due to 99.48% are Ecuadorian nationality, with 56.40% between 21 and 30 age years and with an equal distribution between genders, in the same way, 45, 17% are residents from Latacunga city, indicating that the festivity is clearly local. Their travel form is mainly in family with an average expense $30 per day with a 41.17%, which spend with their family. The current occupation tourists is students with 37.34%. Their marital status: 67.10% are single. The main reason for traveling, it is reunions with family and friends. Moreover, it was elaborated the Pearson's chi-square coefficient between different sociodemographic and socioeconomic variables to determine the significance between two variables. Subsequently, it was made the third aim, it was applied the descriptive-relational research type with a quantitative approach, it was elaborated the academic article proposal, which they got results are covered, this was made based on the scientific journal structure (Tourism notebooks), it has as purpose to disseminate articles about geographical, urban planning, economic, ecological and training aspects related to tourist activity. Concluding, what the Mama Negra of September month has cultural value for the Latacungueños, likewise those, who attend the celebration from Mama Negra are Ecuadorian nationality who travel with their family.